(untitled) (American Journal of Islam and Society, 2004)
If the real value of a book – any book – comes from its ability to present itself as a subject of various, but not contradictory, readings, this book undoubtedly fulfils that value. From the point of view of a Muslim and nonwestern reader, the book reflects the western fear of Islam as a power in crisis but adopts a line of argument against mainstream western writings on Islam. In other words, it argues against the prevalent claim that Islam, especially after the collapse of communism, represents the most dangerous threat to western values. Further, the book suggests that “opportunities for positive engagement with Africa’s Muslim communities and states abound on the political, social, religious, economic, and cultural level” (p. 150). Motivated by the need “to find a reasonable avenue of exploration and accommodation with countries and cultures that differ from our own (the Western culture),” the book unveils the mutual misunderstanding between the West and the Muslim world. Thus, it argues that the “Muslim world is treated (by the West) as having a single dimension, as if Muslims in general had bonded with Osama bin Laden” (p. 4). It also argues that the West sees Muslims as “stubbornly holding the idea that Christians have not abandoned the Crusaders’ mentality, zealously trying to destroy all traces of Muslim civilizations in their entirety” (p. 4). Being aware of the harmful impacts of these misleading images not only on the media, but also – and this is the most dangerous – on the “contemporary (academic) analysis,” the book invites the People of the Book (ahl al-kitab) to work together toward peace and reconciliation, emphasizing that “it will be a difficult but not impossible road.” Without this effort to make peace, the book suggests, there will be chaos and violence ...